Peningkatan Literasi Pembukuan dan Kepatuhan Pajak UMKM Kuliner - Umi Nandiroh; Jeni Susyanti (GUYUB: Journal of Community Engagement, 2025)
This community service program addresses a critical gap: low tax compliance among culinary micro and small enterprises (MSMEs) in Malang City, which restricts access to finance and weakens local revenue. We aimed to improve bookkeeping literacy and tax compliance through an integrated intervention—classroom instruction (tax fundamentals), hands-on simple bookkeeping, guided use of a tax application (Coretax), and mentoring—for 15 MSME owners. Effectiveness was assessed using pre–post knowledge tests, observation checklists of bookkeeping practices, and application usage logs as compliance indicators. Results show a marked increase in knowledge and self-efficacy (mean Likert score 2.7→4.2). Adoption of basic/digital bookkeeping improved: 85% of participants began daily transaction recording and separated business–personal finances. Most participants were able to compute and file taxes using the application, and post-training compliance reached 66.7% (10 of 15) based on verified filings within the evaluation period. The bookkeeping model promoted includes a daily cash book, separation of business and personal accounts, and simple records of inventory and production costs as the basis for tax calculation. These findings indicate that coupling financial literacy with accessible technology can shift administrative behavior and improve compliance. Replication should include follow-up mentoring and partnerships with local authorities to sustain results